Hölder continuity and the Harnack inequality for the solutions of an elliptic equation containing the p -Laplacian and uniformly degenerating in a part of the domain - Huseynov, S. T. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We consider quasilinear equations of the p-Laplacian type uniformly degenerating in a part of the domain. An analog of the Harnack inequality is proved for nonnegative solutions and the Holder continuity of the solutions is established by using this inequality.